APPLICATION OF SLOW STEAMING ON 100 TEUs CONTAINER SHIP ON THE TANJUNG PERAK-BELAWAN ROUTE - Fajar Andinuari; Adi Sasmito Aji; Vialdo Muhammad Virmansyah; Rr. Niken Danartika Hadi Putri (Journal of Marine-Earth Science and Technology, 2024)
Sea transportation is a vital component of international trade, constituting over 80% of global cargo movement. As the shipping sector anticipates a promising future amid economic liberalization and enhanced operational efficiency, the focus on reducing fuel consumption becomes paramount. This paper investigates the potential benefits and drawbacks of implementing slow steaming, a strategy involving reduced ship speeds, to curtail operational costs, particularly fuel expenses that constitute 47% of total ship operational costs. The liner shipping industry in Indonesia is examined as a case study, evaluating the impact of slow steaming on fuel consumption, emissions, and overall financial performance. Ship that was used in this paper is a 100 TEUs container ship with 2 x 1550 HP engine Yanmar 12AYM-WET which had a voyage route that is assumed to be direct from Tanjung Perak Port to Belawan Port without any transit at other ports. There are 6 speed variations from sea trial data to calculating fuel consumption. Another assumption used is that the dwelling time at Belawan port as of December 2023 is 2.89 days. Considering the dwelling time at Belawan Port, Medan, the speed chosen is 7.6 knots with a travel time of 8.16 days. The assumption is that the fuel used is Diesel Oil B35 with a price of Rp. 22,300/litre. The fuel savings with a travel time of 8.16 days is 19,283.13 litres. The RPM ratio in existing conditions is 1:1.3. So the conversion is carried out into a graph to get the existing FOC. Next, the FOC calculation is carried out by interpolating the fuel consumption diagram against RPM. The CII value at a speed of 7.6 knots shows 0.593 with an A rating. The EEXI value when the speed is 7.6 knots shows the number 7.1235 which is compliant.